Biomechanical evaluation of a new gliding screw concept for the fixation of proximal humeral fractures. Issue 6 (June 2018) - Acklin, Y. P.; Zderic, I.; Inzana, J. A.; Grechenig, S.; Schwyn, R.; Richards, R. G.; Gueorguiev, B.
Abstract : Aims: Plating displaced proximal humeral fractures is associated with a high rate of screw perforation. Dynamization of the proximal screws might prevent these complications. The aim of this study was to develop and evaluate a new gliding screw concept for plating proximal humeral fractures biomechanically. Methods: Eight pairs of three-part humeral fractures were randomly assigned for pairwise instrumentation using either a prototype gliding plate or a standard PHILOS plate, and four pairs were fixed using the gliding plate with bone cement augmentation of its proximal screws. The specimens were cyclically tested under progressively increasing loading until perforation of a screw. Telescoping of a screw, varus tilting and screw migration were recorded using optical motion tracking. Results: Mean initial stiffness (N/mm) was 581.3 (sd 239.7) for the gliding plate, 631.5 (sd 160.0) for the PHILOS and 440.2 (sd 97.6) for the gliding augmented plate without significant differences between the groups (p = 0.11). Mean varus tilting (°) after 7500 cycles was comparable between the gliding plate (2.6; sd 1.9), PHILOS (1.2; sd 0.6) and gliding augmented plate (1.7; sd 0.9) (p = 0.10). Similarly, mean screw migration(mm) after 7500 cycles was similar between the gliding plate (3.02; sd 2.85), PHILOS (1.30; sd 0.44) and gliding augmented plate (2.83; sd 1.18) (p = 0.13). Mean number of cycles until failure with 5° varus tilting were 12702 (sd 3687) for the gliding plate, 13948 (sd 1295) for PHILOS and 13189 (sd 2647) for the gliding augmented plate without significant differences between the groups (p = 0.66). Conclusion: Biomechanically, plate fixation using a new gliding screw technology did not show considerable advantages in comparison with fixation using a standard PHILOS plate. Based on the finding of telescoping of screws, however, it may represent a valid approach for further investigations into how to avoid the cut-out of screws. Cite this article : Y. P. Acklin, I. Zderic, J. A. Inzana, S. Grechenig, R. Schwyn, R. G. Richards, B. Gueorguiev. Biomechanical evaluation of a new gliding screw concept for the fixation of proximal humeral fractures. Bone Joint Res 2018;7:422–429. DOI: 10.1302/2046-3758.76.BJR-2017-0356.R1.